MODIFICATION OF PURUN TIKUS (ELEOCHARIS DULCIS) AS A NATURAL FIBER COMPOSITE USING KMnO4 AND NaOH - Ninis Hadi Haryanti; Suryajaya Suryajaya; Lies Banowati; Mawaddatur Rahmah; Akhmad Safi'i (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
The choice of natural fibers as a composite reinforcing material is related to the advantages of being cheap, abundant, renewable, and environmentally friendly. This research was conducted to study the effect of de-lignification treatment on the properties of purun tikus (Eleocharis Dulcis) fiber. Purun tikus fiber has been modified with the alkaline treatment of KMnO4 2% and NaOH 5%. This treatment was mainly applied to improve the physical and chemical properties of purun tikus fiber. Changes in chemical characteristics (water, lignin, cellulose, and hemicellulose), physical (density), mechanical (tensile strength), morphology, and elemental content of purun tikus before and after treated with alkaline were studied. The measurements showed an increase in water content and density while lignin, cellulose, and hemicellulose were decreased. Thus the alkaline treatment of KMnO4 2% and NaOH 5% reduced lignin, cellulose, and hemicellulose of the purun tikus fiber to reduce the size of the fibers, as shown in SEM measurements. There was a change in elemental content after being treated with KMnO4 2% and NaOH 5%. NaOH treatment was better than KMnO4 treatment in terms of removing lignin and hemicellulose in purun tikus fiber. Although the tensile strength of the purun fibers treated with KMnO4 2% and NaOH 5% were lower than untreated, with less lignin, cellulose, and hemicellulose, it is expected that these fibers will blend better in the composite and improved its mechanical properties.